2005
DOI: 10.5688/aj690104
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Professional Development: A Qualitative Study of Pharmacists' Attitudes, Behaviors, and Preferences in Ontario, Canada

Abstract: Objectives. The purpose of this study was to examine pharmacists' attitudes, behaviors, and preferences towards continuous professional development in Ontario, Canada. Methods. A series of 11 focus group sessions were undertaken with groups of 4 to 5 different pharmacists participating in the Ontario College of Pharmacists' Quality Assurance and Peer Review Process Learning Portfolio session. During these sessions, extensive field notes were compiled and verified with participants. Following all sessions, fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
115
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(120 citation statements)
references
References 10 publications
1
115
0
Order By: Relevance
“…8 Those pharmacists who were initially familiar with CPD endorsed the model for their peers, and suggested it had made a meaningful difference in the way they viewed their own practice. In virtually all focus groups sessions, pharmacists familiar with and supportive of the CPD paradigm had worked in collaborative practice environments such as hospital pharmacy practice.…”
Section: Data From Focus Groupsmentioning
confidence: 99%
“…8 Those pharmacists who were initially familiar with CPD endorsed the model for their peers, and suggested it had made a meaningful difference in the way they viewed their own practice. In virtually all focus groups sessions, pharmacists familiar with and supportive of the CPD paradigm had worked in collaborative practice environments such as hospital pharmacy practice.…”
Section: Data From Focus Groupsmentioning
confidence: 99%
“…28,35,36,39,40 Of these, two were conducted using the same cohort of pharmacists in Ontario, Canada. 28,35 The Canadian studies identified a variation in the number of reported changes to practice. These changes were based on a self-report questionnaire, a data-collection method that has a number of limitations.…”
Section: Discussionmentioning
confidence: 99%
“…35 The QAPR also includes sharing the contents of a portfolio after submission to staff members of the Ontario College of Pharmacists. Participants commented that the portfolio was useful for identifying learning gaps.…”
Section: A Signpost For Learningmentioning
confidence: 99%
“…Indeed, most people are aware they don't do it well. 13 With time and practice, people can master the tactics and strategies needed to be life-long learners.…”
Section: R a F Tmentioning
confidence: 99%